To the inhabitants of the city and county of New-York : the wisest men in all ages, have observed and laid it down as a maxim, that whatever may be the particular opinions of individuals, the bulk of the people, both mean, and think right . - Citizen, 1716-1778 (LLMC-digital (Series), 1775)
Urging attendance at the meeting on Monday, March 6, to determine the means of choosing delegates to the Continental Congress, and recommending a provincial congress.